PENGARUH PENAMBAHAN ASTAXANTHIN DALAM PENGENCER AIR KELAPA MUDA KUNING TELUR TERHADAP KUALITAS SEMEN CAIR SAPI ANGUS (Effect of adding astaxanthin in egg yolk young coconut water on the quality of liquid semen of angus bull) - Kurouma, Mario Saturninus; Belli, Henderiana; Kihe, Johny N.; Nalley, Wilmientje M. (JURNAL NUKLEUS PETERNAKAN, 2024)
Artificial insemination (AI) is an appropriate technology that can be used to increase the productivity of cattle. The application of AI technology can use frozen semen, fresh semen or liquid semen. Semen quality as an important factor in the success of AI is influenced by the cement processing process starting from the collection, dilution, and preservation of cement. This study was conducted to determine the effectiveness of young coconut water-egg yolk diluent added with astaxanthin in maintaining motility, viability, abnormalities and survival of Angus cattle spermatozoa. Semen was collected from an angus bull about three years old who had previously been trained to collect semen with an artificial vagina. Semen of good quality is diluted with coconut water-egg yolk (CW-EY) with the addition of astaxanthin (As) at doses: 0 (T0), 0.25g (T1), 0.50g (T2), and 0.75g (T3) ). Semen was stored at 3-5ºC after being diluted, and evaluation of the quality of spermatozoa was carried out every 24 hours. Each treatment was repeated five times to form 20 experimental units. The results showed that spermatozoa in CW-EY diluent with the addition of As 0.25g (T1) compared to the other three treatments had higher quality (P<0.05), namely with motility reaching (35.50 ± 2.12% ), viability (47.41 ± 3.26%), abnormality (6.16 ± 1.51%) and survival (5.00 ± 0.00 days). The conclusion in this study was that the addition of 0.25g of astaxanthin in CW-EY diluent was effective in maintaining the quality of liquid semen of Angus cattle.